Virtual tissue alignment and cutting plane definition – a new method to obtain optimal longitudinal histological sections. Issue 2 (25th November 2013) - Danz, J. C.; Habegger, M.; Bosshardt, D. D.; Katsaros, C.; Stavropoulos, A.
Abstract Histomorphometric evaluation of the buccal aspects of periodontal tissues in rodents requires reproducible alignment of maxillae and highly precise sections containing central sections of buccal roots; this is a cumbersome and technically sensitive process due to the small specimen size. The aim of the present report is to describe and analyze a method to transfer virtual sections of micro‐computer tomographic (CT)‐generated image stacks to the microtome for undecalcified histological processing and to describe the anatomy of the periodontium in rat molars. A total of 84 undecalcified sections of all buccal roots of seven untreated rats was analyzed. The accuracy of section coordinate transfer from virtual micro‐CT slice to the histological slice, right–left side differences and the measurement error for linear and angular measurements on micro‐CT and on histological micrographs were calculated using the Bland–Altman method, interclass correlation coefficient and the method of moments estimator. Also, manual alignment of the micro‐CT‐scanned rat maxilla was compared with multiplanar computer‐reconstructed alignment. The supra alveolar rat anatomy is rather similar to human anatomy, whereas the alveolar bone is of compact type and the keratinized gingival epithelium bends apical to join the junctional epithelium. The high methodological standardization presented herein ensures retrieval of histological slices with excellent display of anatomical microstructures, in a reproducible manner, minimizes random errors, and thereby may contribute to the reduction of number of animals needed.